2008
DOI: 10.1016/j.pain.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture modulates resting state connectivity in default and sensorimotor brain networks

Abstract: Previous studies have defined low-frequency, spatially consistent networks in resting fMRI data which may reflect functional connectivity. We sought to explore how a complex somatosensory stimulation, acupuncture, influences intrinsic connectivity in two of these networks: the default mode network (DMN) and sensorimotor network (SMN). We analyzed resting fMRI data taken before and after verum and sham acupuncture. Electrocardiography data were used to infer autonomic modulation through measures of heart rate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
243
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 263 publications
(260 citation statements)
references
References 62 publications
12
243
2
3
Order By: Relevance
“…Transcutaneous electrical nerve stimulation (TENS) on the median nerve induced SEPs, resulting in delayed gating effects on cortical response (Torquati et al, 2007). TENS also broadly modulated sensorimotor brain network activity, including the somatosensory cortex, basal ganglia, and thalamus (Choi et al, 2016;Dhond et al, 2008;Fang et al, 2009;Kara et al, 2010), and cortical neuronal excitability (Veldman et al, 2014). It appears that TENS, in particular TEAS, is capable of repairing filtering' dysfunction of the sensorimotor gating via enhancing 5-HT and neuropeptide functions in related brain regions.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) on the median nerve induced SEPs, resulting in delayed gating effects on cortical response (Torquati et al, 2007). TENS also broadly modulated sensorimotor brain network activity, including the somatosensory cortex, basal ganglia, and thalamus (Choi et al, 2016;Dhond et al, 2008;Fang et al, 2009;Kara et al, 2010), and cortical neuronal excitability (Veldman et al, 2014). It appears that TENS, in particular TEAS, is capable of repairing filtering' dysfunction of the sensorimotor gating via enhancing 5-HT and neuropeptide functions in related brain regions.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…(2)). Similarly, acupuncture, not the sham condition, can also induce the increased connectivity within both the default mode network and sensorimotor network [35], including the medial temporal lobe, PAG and supplementary motor area (SMA). They also reported that connectivity between the hippocampus and the DMN saliently correlated with parasympathetic output only following the acupuncture stimulation.…”
Section: Sustained Effects Of Acupuncture and Its Influence On Fmri Rmentioning
confidence: 99%
“…And also a great idea: opioids regulate default network, the resting state active areas that are responsible for our consequent conditions of body-mind -study by Dhond [12] in 2008…”
Section: Main Text and Discussionmentioning
confidence: 99%